2003
DOI: 10.1021/jp0350666
|View full text |Cite
|
Sign up to set email alerts
|

Relaxivity Studies on Dinitroxide and Polynitroxyl Functionalized Dendrimers:  Effect of Electron Exchange and Structure on Paramagnetic Relaxation Enhancement

Abstract: The 1 H NMR relaxivity of o-and p-dinitroxide-substituted phthalate esters and a series of nitroxyl-functionalized poly(propylene imine) dendrimers has been measured in acetonitrile and methanol. Studies of dinitroxide relaxivity indicate that the electron exchange rate has only a small effect on relaxivity. Outer-sphere relaxivity has been measured using benzene as a probe molecule. In studies on dendritic polynitroxides, the per-nitroxidebased outer-sphere relaxivity nearly doubles for the generation 5 nitro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 37 publications
(140 reference statements)
1
33
0
Order By: Relevance
“…2-(1H-Benzotriazole-1-yl)-1,1,3,3-tetramethyluronium hexafluorophosphate (HBTU) was purchased from Iris Biotech GmbH (Germany). The first and third generations of amine-terminated poly(propylene imine) dendrimers [DAB-dendr-(NH 2 ) n , n ¼ 4 and 16] were kindly provided by SyMO-Chem (Eindhoven, the Netherlands) (46). Cyclen was obtained from ABCR GmbH (Karlsruhe, Germany).…”
Section: Experimental General Proceduresmentioning
confidence: 99%
“…2-(1H-Benzotriazole-1-yl)-1,1,3,3-tetramethyluronium hexafluorophosphate (HBTU) was purchased from Iris Biotech GmbH (Germany). The first and third generations of amine-terminated poly(propylene imine) dendrimers [DAB-dendr-(NH 2 ) n , n ¼ 4 and 16] were kindly provided by SyMO-Chem (Eindhoven, the Netherlands) (46). Cyclen was obtained from ABCR GmbH (Karlsruhe, Germany).…”
Section: Experimental General Proceduresmentioning
confidence: 99%
“…60 Relaxivity studies on dinitroxides and dendritic nitroxide multiradicals (46, Scheme 5.15) have been performed. 61 Dendritic polynitroxides exhibit higher per-nitroxide-based water relaxivity compared to a mononitroxide model. The higher generation polynitroxide dendrimers exhibit relaxivities exceeding those for gadolinium(III) chloride.…”
Section: Miscellaneous Aspects Of Di-and Polynitroxidesmentioning
confidence: 99%
“…A prefluorescent hydrophobic TEMPO derivative has been used to evaluate local reactivity of phenolic antioxidant in micellar systems 263 (Scheme 5. 61). An apparent rate constant that directly reflects the relevance of antioxidant hydrophobicity on the reaction toward the nitroxide has been defined.…”
Section: Interaction Of Nitroxides With Micellesmentioning
confidence: 99%
“…An interesting study of potential dendrimer-based MRI contrast agents, that was not based upon the proton relaxation enhancing properties of gadolinium, was carried out by Meijer and co-workers [46]. Proton relaxation studies were carried out on nitroxyl bearing PPI dendrimers (Figure 8.6) and revealed that as a result of an increased rotational correlation time, the dendrimer architecture conferred an enhanced proton relaxation on the nitroxyl moieties when compared to mononitroxyl species.…”
Section: Dendritic Medical Imaging Systemsmentioning
confidence: 99%
“…The nitroxyl terminated dendrimer proton relaxation enhancement agent for potential use in MRI[46]. A water-soluble functionalised tin-based metallodendrimer developed for applications in X-ray scanning[47].…”
mentioning
confidence: 99%